Current preventive strategies and management of Epstein–Barr virus-related post-transplant lymphoproliferative disease in solid organ transplantation in Europe. Results of the ESGICH Questionnaire-based Cross-sectional Survey. (June 2015) - San-Juan, R.; Manuel, O.; Hirsch, H.H.; Fernández-Ruiz, M.; López-Medrano, F.; Comoli, P.; Caillard, S.; Grossi, P.; Aguado, J.M.
Abstract: There is limited clinical evidence on the utility of the monitoring of Epstein–Barr virus (EBV) DNAemia in the pre-emptive management of post-transplant lymphoproliferative disease (PTLD) in solid organ transplant (SOT) recipients. We investigated current preventive measures against EBV-related PTLD through a web-based questionnaire sent to 669 SOT programmes in 35 European countries. This study was performed on behalf of the ESGICH study group from the European Society of Clinical Microbiology and Infectious Diseases. A total of 71 SOT programmes from 15 European countries participated in the study. EBV serostatus of the recipient is routinely obtained in 69/71 centres (97%) and 64 (90%) have access to EBV DNAemia assays. EBV monitoring is routinely used in 85.9% of the programmes and 77.4% reported performing pre-emptive treatment for patients with significant EBV DNAemia levels. Pre-emptive treatment for EBV DNAemia included reduction of immunosuppression in 50.9%, switch to mammalian target of rapamycin inhibitors in 30.9%, and use of rituximab in 14.5% of programmes. Imaging by whole-body 18-fluoro-deoxyglucose positron emission tomography (FDG-PET) is used in 60.9% of centres to rule out PTLD and complemented computer tomography is used in 50%. In 10.9% of centres, FDG-PET is included in the first-line diagnostic workup in patients with high-risk EBV DNAemia. Despite the lack of definitive evidence, EBV load measurements are frequently used in Europe to guide diagnostic workup and pre-emptive reduction of immunosuppression. We need prospective and controlled studies to define the impact of EBV monitoring in reducing the risk of PTLD in SOT recipients.